Hierarchical distribution of somatic variants in newly diagnosed chronic myeloid leukaemia at diagnosis and early follow-up - Romžová, Marianna; Smitalova, Dagmar; Hynst, Jakub; Tom, Nikola; Loja, Tomas; Herudkova, Zdenka; Jurcek, Tomas; Stejskal, Lukas; Zackova, Daniela; Mayer, Jiri; Racil, Zdenek; Culen, Martin (British journal of haematology, 2021)
There is an emerging body of evidence that patients with chronic myeloid leukaemia (CML) may carry not only breakpoint cluster region-Abelson murine leukaemia viral oncogene homologue 1 (BCR-ABL1) kinase domain mutations (BCR-ABL1 KD mutations), but also mutations in other genes. Their occurrence is highest during progression or at failure, but their impact at diagnosis is unclear. In the present study, we prospectively screened for mutations in 18 myeloid neoplasm-associated genes and BCR-ABL1 KD in the following populations: bulk leucocytes, CD34+ CD38+ progenitors and CD34+ CD38- stem cells, at diagnosis and early follow-up. In our cohort of chronic phase CML patients, nine of 49 patients harboured somatic mutations in the following genes: six ASXL1 mutations, one SETBP1, one TP53, one JAK2, but no BCR-ABL1 KD mutations. In seven of the nine patients, mutations were detected in multiple hierarchical populations including bulk leucocytes at diagnosis. The mutation dynamics reflected the BCR-ABL1 transcript decline induced by treatment in eight of the nine cases, suggesting that mutations were acquired in the Philadelphia chromosome (Ph)-positive clone. In one patient, the JAK2 V617F mutation correlated with a concomitant Ph-negative myeloproliferative neoplasm and persisted despite a 5-log reduction of the BCR-ABL1 transcript. Only two of the nine patients with mutations failed first-line therapy. No correlation was found between the mutation status and survival or response outcomes.
Keywords: mutace; Fusion Proteins, bcr-abl; Follow-Up Studies; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; prognóza; prospektivní studie; lidé; chronická myeloidní leukemie; Mutation; bcr-abl fúzní proteiny; Prognosis; následné studie; Prospective Studies